2015
DOI: 10.1159/000438760
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Chronic Parotitis: Imaging Findings and Sialendoscopic Response

Abstract: Background/Aims: The purpose of this study was to correlate imaging and sialendoscopic findings to therapeutic response in patients with idiopathic chronic parotitis. Methods: We retrospectively reviewed 122 consecutive sialendoscopies performed in an academic medical center by two surgeons between 2008 and 2013. Forty-one (34%) and 54 (44%) patients were excluded on the basis of having parotid or submandibular sialolith, respectively. Nineteen cases were included in the study with idiopathic chronic parotitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Most prior studies on sialendoscopic therapies for salivary duct stenosis examined symptoms of gland pain and swelling . The COSS questionnaire used in this study provides an expanded query of sialadenitis‐specific symptoms and demonstrated 15 of 20 symptoms improved after SASDS, including pain frequency, pain severity, tenderness frequency, tenderness severity, swelling frequency during meals, swelling severity during meals, swelling frequency between meals, swelling severity between meals, noticeability by others, embarrassment, xerostomia, too much saliva, ability to speak, ability to chew, and ability to engage in daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior studies on sialendoscopic therapies for salivary duct stenosis examined symptoms of gland pain and swelling . The COSS questionnaire used in this study provides an expanded query of sialadenitis‐specific symptoms and demonstrated 15 of 20 symptoms improved after SASDS, including pain frequency, pain severity, tenderness frequency, tenderness severity, swelling frequency during meals, swelling severity during meals, swelling frequency between meals, swelling severity between meals, noticeability by others, embarrassment, xerostomia, too much saliva, ability to speak, ability to chew, and ability to engage in daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Vashishta et al showed the majority of endoscopic findings include stenosis or strictures, and general symptom improvement was reported in 88% of 51 patients . Heineman et al showed that 74% of patients with idiopathic parotitis had partial or complete response for symptomatic pain and swelling after sialendoscopy . Both of these studies evaluated general improvement or changes in gland pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Definable causes of chronic sialadenitis include Sjögren's syndrome, HIV‐associated diffuse infiltrative lymphocytosis, radioiodine‐induced sialadenitis (Wu et al , ), chronic graft‐versus‐host disease (Drew et al , ), and sarcoidosis. ‘Idiopathic chronic parotitis’, ‘chronic recurrent parotitis’, and ‘juvenile recurrent parotitis’ commonly designate chronic salivary gland inflammation without a definable cause (Baurmash, ; Heineman et al , ). Although these are most likely heterogeneous disorders, their features overlap with ‘eosinophilic sialodochitis’, with a similar average age at presentation for the adult forms, female preponderance, and clinical and radiographic features.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…These methods have the potential to control the symptoms in mild cases [8]. However, there are only few studies published on conservative treatment, [1] and the number of studies on the treatment of chronic recurrent parotitis with sialendoscopy is also limited [11,14,15]. Therefore, we performed a prospective study on 49 adult patients with chronic recurrent parotitis to evaluate the efficacy of sialendoscopy with or wihtout a concurrent singledose intraductal corticosteroid.…”
Section: Discussionmentioning
confidence: 99%